2007
DOI: 10.1177/147078530704900108
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Food Markets - The Role of Ethnocentrism and Lifestyle in Understanding Purchasing Intentions

Abstract: Previous research on ethnocentrism and lifestyle has focused on attitudinal segmentation. However, consumer attitudes may not always be consistent with the actual purchasing decision. Since behavioural intentions are more proximal predictors of behaviours than attitudes, segmenting markets using purchasing intentions might be more appropriate. The purpose of this study is to use purchasing intention to examine whether lifestyle and ethnocentrism can be useful indicators in segmenting foreign and domestic food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 26 publications
9
70
0
14
Order By: Relevance
“…Examples of these studies include studies conducted with samples from Japan and West Germany (Netemeyer et al, 1991); Poland (Good & Huddleston, 1995;Supphellen & Rittenburg, 2001;Huddleston, Good & Stoel, 2001); Malta (Caruana & Magri, 1996); Korea (Sharma et al, 1995); Russia (Good & Huddleston, 1995;Saffu & Walker, 2005) and Turkey (Kavak & Gumusluoglu, 2007 …”
Section: The Reliability Of the Cetscalementioning
confidence: 99%
“…Examples of these studies include studies conducted with samples from Japan and West Germany (Netemeyer et al, 1991); Poland (Good & Huddleston, 1995;Supphellen & Rittenburg, 2001;Huddleston, Good & Stoel, 2001); Malta (Caruana & Magri, 1996); Korea (Sharma et al, 1995); Russia (Good & Huddleston, 1995;Saffu & Walker, 2005) and Turkey (Kavak & Gumusluoglu, 2007 …”
Section: The Reliability Of the Cetscalementioning
confidence: 99%
“…Marketers have developed different ways of identifying consumers' characteristics, dividing consumers into groups and analysing consumer behaviour towards a certain product. Socioeconomic and demographic features such as age, gender, standard of living and education have been widely used to segment markets (Plummer, 1974;Kavak and Gumusluoglu, 2006). However, the rapid rate of change in Western economies, the economic crisis and the massive rise in the popularity of Information and communication technologies mean that the socioeconomic and demographic characteristics traditionally used to explain consumer behaviour are no longer effective (González, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have found strong statistical evidence for the direct negative link between CET and willingness to buy foreign products (e.g., Klein et al, 1998;Suh & Kwon, 2002). According to Kavak and Gumusluoglu (2007), "ethnocentric consumers do not approve of purchasing a foreign-made product, since they think it is harmful to the domestic economy and employment; it would put domestic producers at a disadvantage, which, in turn, would increase unemployment and worsen economic conditions in the home country." Since unknown food is unfamiliar because its ingredients do not belong to the native or local range of foods, and therefore usually comes from abroad, it is possible to hypothesize that consumer ethnocentrism could play a significant moderator role in the acceptance and intention to try that type of unfamiliar food.…”
Section: Consumer Ethnocentrismmentioning
confidence: 96%